Partial food systems baseline assessment at the Vietnam benchmark sites - Huynh Thi Thanh Tuyen; Pham, Huong Thi Mai; Trinh, Huong Th; Duong, Thanh Thi; Nguyen, Trang Mai; Hernández, Ricardo; Lundy, Mark M.; Nguyen, Kien Tri; Nguyen, Lam Le Tun; Vuong, Vy Thao; Nguyen, Ha Thu; Truong, Mai Tuyet; et al. (2021)
Using data collected from a cross-sectional study in Moc Chau, Dong Anh and Cau Giay districts in Vietnam, this report aims to elucidate specific components of local Vietnamese food systems along a rural to urban transect focusing specifically on (i) diets, (ii) nutrition status (anthropometry), (iii) consumer behavior, (iv) food environment, and (v) food flows.